19. THE CURRENT STATUS OF SCHOOL STUDENTS WITH MYOPIA AT THANH LIET SECONDARY SCHOOL, THANH TRI, HANOI, IN 2022, AND MYOPIA-RELATED FACTORS (Vietnam Journal of Community Medicine, 2023)
Objectives: (i) To assess the situation of myopia in schools of students at Thanh Liet secondaryschool, Thanh Tri, Hanoi in 2022; (ii) Analysis of some factors related to the current situation ofschool myopia of the study subjects.Subjects - Methods: Students from grades 6 to 9, conduct a simple random sampling: select 3classes/block by lottery and select all students of classes participating in the study including 420students. Methods: A cross-sectional description with analysis and use of secondary data.Result: As a result, there were 420 students participating in the study, accounting for 55.5% ofmyopia. In which, 57.5% of students with myopia do not wear glasses. The average age at beingdiagnosed with myopia among students participating in the study was 9.0 (±2.6). Female studentsare 1.5 times more likely to have myopia than male students (95% CI: 1.0 - 2.3; p
Keywords: Myopia, myopia-related, prevalence.